The Hungarian Blasphemy Cases Free Speech v. Protection of Religious Communities - Csink Lóránt; Trócsányi László (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2024)
Free speech is a cornerstone of democracy. So as cultural diversity and the protection of various reli gious communities. But what if they compete? How to handle situations when expressions infringe religions or religious people? Recently, such questions have become crucial for legal literature and jurisprudence. The present paper does not have a definite answer which democratic value to the first place. Instead, it intends to give aspects upon which the issue can be determined. For this purpose the paper first gathers the different approaches and describes the differences of several national courts and the ECtHR. Then it analyses the recent case law of the Hungarian Constitutional Court, finally it draws conclusions.